2022
DOI: 10.13005/bpj/2460
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oral Supplementation of Damiana (Turnera diffusa) Reduces the Renal Toxicity, Apoptosis and DNA Damage Associated with Amitriptyline Administration in Rats

Abstract: Major depressive disorder and anxiety disorders are two mental diseases that are treated with amitriptyline (AMT). AMT treatments induced liver, heart and testes toxicity; As a result, the purpose of this study was to determine the preventative and therapeutic role of damiana (Dam) as adjuvant herbal therapy against AMT induced heart injury in rats. Six groups of 36 rats (male albino) were randomly assigned; first one is control, second is Dam, third was AMT, fourth was Dam+AMT, fifth was AMT+Dam and sixth was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Our findings also corroborate the findings of Hoseini et al [29] and Tousson et al [37], which showed that nandrolone decanoate caused renal impairment in mice. Treatment with herbal medicine improved kidney function and structure [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also corroborate the findings of Hoseini et al [29] and Tousson et al [37], which showed that nandrolone decanoate caused renal impairment in mice. Treatment with herbal medicine improved kidney function and structure [38].…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the two univalent cations of fundamental physiological relevance, potassium, and sodium, throughout the body is one of the kidney's key roles (Alm-Eldeen and Tousson, 2012;Hasan et al, 2022). The metabolism of calcium is a subject that the kidney takes very seriously (Salama et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The liver and brain tissues of all groups were excised, fixed in 10% formalin for a period between (24-48 hours), dehydrated in ascending alcohol concentrations, paraffin wax infiltrated and then were cut at 5 m sections to be mounted on glass slides. Then, the slide tissue sections were deparaffinized and hydrated again then stained with hematoxylin and eosin (H&E) for histological examination by light microscopy according to Hameed et al (2022) andFatoh et al (2023).…”
Section: Immunohistochemical Investigationmentioning
confidence: 99%